Analisis Hubungan Pertumbuhan Ekonomi dengan Kemiskinan dan Belanja Modal Pemerintah Daerah, Penyerapan Tenaga Kerja, dan Indeks Pembangunan Manusia - Hardana, Ali (Studi Ekonomi dan Kebijakan Publik, 2024)
Purpose: This study examines the effects of local governments’ capital expenditures, labor absorption, and the Human Development Index on economic growth and poverty in 35 districts/cities in Central North Sumatra. Methodology/Approach: Quantitative research was used in this study. The secondary data were used by the researchers. Capital expenditures of local governments, labor absorption, and the Human Development Index are exogenous variables, while economic growth and poverty level are endogenous variables. Results: The results showed that the four proposed hypotheses were accepted, and the hypothesis was rejected. Limitations: Ownership structure and ownership have no relationship with debt policies. Contributions: Nasution et al. (2023) The results showed that the four proposed hypotheses were accepted and the hypothesis was rejected. Hypothesis 1 suggests that local government capital expenditures have a significantly positive effect on economic growth. Hypothesis 2 suggests that labor absorption has a significantly positive effect on economic growth. Hypothesis 3 suggests that the Human has a significantly positive effect on economic growth. Hypothesis 4 suggests that economic growth has no significant effect on poverty. Hypothesis 5 suggests that the Human Development Index has a significantly negative effect on poverty.Index is a significantly negative effect on poverty.